Influence of pulse plasma treatment on the phase composition and microhardness of detonation coatings based on Ti-Si-C - Б.K. Рахадилов; Д.Б. Буйткенов; М. Адилханова; Ж.Б. Сагдолдина; Ш.Р. Курбанбеков (Қарағанды университетінің хабаршысы. Физика сериясы)
The paper considers the study results of the phase composition and microhardness of detonation coatings based on Ti-Si-C after exposure to pulsed plasma treatment. The CCDS2000 detonation complex was used to obtain the coatings. Coatings surface modification was carried out using pulsed plasma exposure (PPE). The detonation coatings were treated with varying the distance H (30 mm mode 1, 40 mm mode 2, 50 mm mode 3) from the plasmatron to the hardened surface. It is shown that the treated coatings are generally characterized by high microhardness compared to the original coating. It was determined that after treatment by pulsed plasma effects an increase in the intensity of all reflexes phase Ti3SiC2 was observed, and the appearance of reflexes (101, 102, 112, 204, 0016) phase Ti3SiC2 was found, which indicates the increase of the content of Ti3SiC2 phase. The change in the fraction of phases indicates a solid-phase transformation during pulsed-plasma activation. High hardness is observed on the coating surface treated according to mode 3 (50 mm) and as it approaches the surface of the substrate modes 2 (40 mm) and 1 (30 mm) the hardness decreases. It is established that the increase in the microhardness of detonation coatings after pulse-plasma treatment is associated with an increase in the content of Ti3SiC2 phases in the coatings, as well as an increase in the defects density in the modified layer.